Inequality during the early years: Child outcomes and readiness to learn in Australia, Canada, United Kingdom, and United States - Bruce Bradbury; Miles Corak; Jane Waldfogel; Elizabeth Washbrook (Institute for the Study of Labor (IZA), 2011)
This study of the emergence of inequality during the early years is based upon a comparative analysis of children at the age of about five years in Australia, Canada, the United Kingdom and the United States. We study a series of child outcomes related to readiness to learn, focusing on vocabulary development and externalizing behavior. Our major findings are three in number. First, significant inequalities in child capacities emerge even in these early years in all four countries but the disparities are notably greater in the United States and the United Kingdom than in Australia, and particularly in Canada. Second, large differences in cognitive outcomes exist in all countries between children from disadvantaged backgrounds and the mainstream and these are of similar magnitudes across countries. Differences across countries in the overall disparity between cognitive outcomes of the least and most advantaged, therefore, largely reflect variation in the degree to which children at the top of the SES distribution out-perform those in the middle. Third, disparities in social and behavioral development are markedly smaller than in cognitive outcomes and differ from cognitive outcomes in their association with SES across countries. While the smallest SES gaps are found in Australia and Canada for both types of outcome, differences in cognitive outcomes are greatest in the US, while differences in behavioral outcomes are greatest in the UK.
urn:nbn:de:101:1-201111303525
Keywords: I24; J13; J24; 330; children; education; socio-economic inequalities; Kinder; Bildungsniveau; Kognition; Familiensoziologie; Soziale Ungleichheit; Vergleich; Australien; Kanada; Großbritannien; USA